(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
The phenomena of modern globalization and internationalization, entering the world educational space not only help to create a multicultural educational space, but also contribute to its multifaceted development. In this thesis, the research level of post-method pedagogy and the definition of the given term by world scientists are analyzed.